Blockchain governance for Virtual Enterprises and Virtual Breeding Environments: a Design Science Research approach - Miranda, Lívia Maria Bettini de (2024)
Governance is an important unit of analysis for partners\' competitive advantage and engagement in value creation as they are involved in collaborative networks of autonomous, geographically distributed, and heterogeneous entities with common goals. Blockchain has emerged as a technological infrastructure for enterprise applications, providing digital governance for organizing inter-organizational relationships. However, a research gap exists in understanding how blockchain can support the organization of joint efforts within collaborative networks, such as Virtual Breeding Environments (VBEs) and Virtual Enter- prises. For this purpose, this study utilizes a Design Science Research approach, guided by Enterprise Modeling methodology, to investigate how blockchain technology can ad- dress inter-organizational collaboration governance requirements of Virtual Enterprises and VBEs. Blockchain governance mechanisms are proposed, including on-chain voting, token-based reputation with an on-chain incentive policy, identity management, and privacy-preserving data sharing. The research empirically validates, statistically tests, provides a simulation analysis, and presents a proof-of-concept implementation of the proposed mechanisms, supporting the design and evaluation of the research artifact referring to a blockchain governance conceptual model. The findings represent preliminary evidence that the proposed mechanisms have generalized utility, highlighting the need for further investigation into blockchain governances relation with traditional contractual and relational safeguards. This study contributes to theory by advancing the understanding of blockchain as an emerging governance mechanism and provides practical insights for practitioners on designing blockchain-enabled governance systems aligned with organizational requirements.